Level of involvement of children and adolescents in various forms of motor activity in Ukraine and member countries Active Healthy Kids Global Alliance - Мандюк, Андрій (Slobozhanskyi Herald of Science and Sport, 2018)
Andriy Mandiuk Purpose: compare the estimates of individual indicators of motor activity in Ukraine and other countries according to the standards of the Active Healthy Kids Global Alliance (AHKGA). Material & Methods: analysis and generalization of scientific literature; methods of the theoretical level of research (analysis and synthesis), a sociological survey, evaluation of data using the Active Healthy Kids Global Alliance methodology. The study was conducted in groups of students aged 12–14 (n=1893, of whom 899 were men and 994 girls) and 15–17 years (n=925, of them 449 men and 476 girls). The assessments of the indicators of the motor activity of children of different ages, presented in the AHKGA database and special reports from different countries. Results: results of a survey of pupils of secondary schools in Ukraine, the analysis of reports on the motor activity of children in the AHKG member countries made it possible to compare the estimates of such indicators of locomotor activity as organized sport and physical activity, unorganized active play, and active transportation. Conclusions: according to AHKGA standards, organized sports activities and motor activity of Ukrainian children are rated for "D", unorganized gaming activity – for "C" and active movement – for "B".